General geology and characterization of framework silicate in Ulu Sokor, Tanah Merah, Kelantan - Nadzirah Khalisah Mohd Zakari (2018)
This research was conducted at Ulu Sokor, Tanah Merah, Kelantan to understand the geology of the study area. The research area was part of the reserved forest Sokor Taku. The objectives for this research were to produce an updated geological map of study area with scale of 1:25,000 and to characterize framework silicate especially quartz and feldspar using petrography and geochemical analysis within the study area. The method used in this study include geological mapping, X-Ray (XRF) and The Scanning Electron Microscope (SEM-EDX) analysis in order to identify the geomorphology, lithologies, geological structure and also for speciﬁcation part in the study area. Based on this research, three types of lithologies found were schist, rnudstone and granite. The oldest lithology identiﬁed was schist that from the Carboniferous-Permian age while the youngest lithology was granite that from Triassic age. All these lithologies can be traced in three formations which were Taku Schist Formation, Telong Formation and Kemahang Granite Formation. Based on XRF analysis for framework silicate of study area give value of 53% to 69% of SiO2. However, the value for F6203 is slightly different as it ranges from 5% to 12% of Fe2O3. Only sample 2 shows the lowest value of F62O3 compared to other samples as it averagely ranged 12%. According to the SEM analysis, the shape of minerals majority show equant shape and bladed shape. Some shapes of mineral are really ruptured and broken but still preserved some originality. Overall, the framework silicates in Ulu Sokor show similar characteristics in terms of element composition and mineral shape.